A Post‐Hoc Comparison of the Utility of Sanger Sequencing and Exome Sequencing for the Diagnosis of Heterogeneous Diseases. Issue 12 (18th October 2013) - Neveling, Kornelia; Feenstra, Ilse; Gilissen, Christian; Hoefsloot, Lies H.; Kamsteeg, Erik‐Jan; Mensenkamp, Arjen R.; Rodenburg, Richard J. T.; Yntema, Helger G.; Spruijt, Liesbeth; Vermeer, Sascha; Rinne, Tuula; van, Koen L.; et al.
<x xml:space="preserve">Abstract</x> In order to determine the impact of exome sequencing in molecular diagnostics, the diagnostic yields for traditional Sanger‐based sequencing and exome sequencing followed by targeted bioinformatics analysis were compared for five genetically heterogeneous disorders. We find that exome sequencing has a much higher diagnostic rate than Sanger sequencing for four of these, being deafness, blindness, mitochondrial disease, and movement disorders. We conclude that exome sequencing is applicable to a broad range of heterogeneous genetic diseases, being an overall effective choice, with respect to both diagnostic yield as well as costs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>